Case Report: Abscopal effect in a patient with refractory metastatic hepatocellular carcinoma treated with stereotactic body radiotherapy and PD-1 inhibitor - Shu, Pei; Wang, Fang; Wang, Xin (Frontiers in Immunology, 2025)
There is currently no established standard treatment for patients with metastatic hepatocellular carcinoma after resistance to tyrosine kinase inhibitors. Given that radiotherapy can reprogram the tumor microenvironment and convert “cold” tumors into “hot” tumors, combining radiotherapy with immunotherapy shows significant potential. In this case, we present a male patient with HBV-related metastatic hepatocellular carcinoma (HCC) accompanied by portal vein tumor thrombosis. The patient achieved abscopal effect with a progression-free survival of 10 months and an overall survival of 21 months with the combination of anti-PD-1 therapy and stereotactic body radiotherapy (SBRT) as third-line treatment. This combination therapy demonstrates relative efficacy and favorability in treating HBV-related advanced HCC.